Prevalence of biopsy proven Lupus Nephritis and outcomes of their treatments in tertiary center in Kuantan - Mohammad Isa, Muhammad Syafiq; Wan Ali, Wan Ahmad Syahril Rozli; Mohamad Nor, Fariz Safhan (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Lupus nephritis (LN) can lead to end stage kidney disease (ESKD) and mortality. Depending on biopsy, induction treatment includes intravenous cyclophosphamide or mycophenolate mofetil with concurrent corticosteroids with the aim to achieve clinical remission at least within 1 year post treatment. This study aims to investigate the prevalence of biopsy proven LN in Hospital Tengku Ampuan Afzan (HTAA) and the outcomes of treatments. Materials and Methods: Retrospective cohort study was conducted among all renal biopsies done in HTAA from 2010 to 2021. Demographic data, clinical presentations, remission status at 1 year and outcomes of treatments were analysed. Cox regression analysis and Kaplan-Meier curve were used respectively to determine the associated risk factors and the rate of progression to ESKD and mortality. Results: There was a total of 177 biopsy proven LN patients from 460 biopsies done making the prevalence of biopsy proven LN in HTAA to be 38.5%. Majority of them were Malays (84.7%), females (89.8%) and less than 40-year-old (85.4%). LN class IV was the commonest presentation (37.9%) and only 9.0% of patients required hemodialysis upon presentation. Renal survival rates at 5- and 10-year of treatment were 92.7% and 90.1% respectively and survival rates at 5- and 10-year of treatment were 85.0% and 80.0% respectively. Hemodialysis requirement upon presentation was associated with progression to ESKD (HR: 5.102, 95% CI: 1.645-15.826, P=0.005) meanwhile treatment compliance was associated with mortality (HR:0.153, 95% CI: 0.0041-0.566, P=0.005). Race, age, gender, LN class and remission status at 1 year post treatment were not associated with poor outcomes. Conclusion: Prevalence of biopsy proven LN in our study is low compared to other studies. Our study had shown higher renal survival rate at 5- and 10-year and lower survival rate at 5- and 10-year. Hemodialysis requirement upon presentation and treatment compliance were associated with poor outcomes.